Serum neurofilament heavy chain predicts post-stroke cognitive impairment - Huimin Qiao; Suhuan Wang; Meichun Tao; Haolong Fan; Tianyi Zhao; Yuanyuan Du; Mei Dong (Scientific Reports)
Abstract Serum phosphorylation neurofilament heavy chain (p-NfH) is a marker of axonal injury, and previous research has shown an association between p-NfH and both Alzheimer’s disease and frontotemporal dementia. However, there have been no reports on its relationship with post-stroke cognitive impairment (PSCI). The purpose of this study is to investigate whether p-NfH can serve as a predictive biomarker for PSCI following acute ischemic stroke (AIS). From July 2020 to September 2021, a total of 58 cases of first-time acute ischemic stroke (AIS) patients were admitted to the Department of Neurology in the Second Hospital of Hebei Medical University. Additionally, 30 healthy volunteers were randomly selected as the control group. Demographic data, medical history, NIHSS scores, cerebral infarction volume, Fazekas scores for white matter and the serum p-NfH were collected. Follow-up assessments were conducted at 6 and 12 months after AIS. Cognitive function was evaluated using a multi-domain cognitive assessment scale, and patients were categorized into the post-stroke cognitive impairment group (PSCI) and non-post-stroke cognitive impairment group (N-PSCI). Further stratification was done into the progression group (MoCA score decline) and stable group (MoCA score unchanged or improved) based on the difference in MoCA scores between 12 and 6 months. The serum p-NfH levels in the AIS group were significantly higher than those in the control group (p < 0.01). Additionally, p-NfH levels were positively correlated with NIHSS scores and infarct volume. Furthermore, AIS patients with moderate to severe cerebral white matter lesions (Fazekas score ≥ 2) showed higher p-NfH levels compared to AIS patients with no or mild white matter lesions (Fazekas score 0 or 1) (p < 0.01). The PSCI group demonstrated higher p-NfH levels compared to the N-PSCI group, even after accounting for variables such as age, education level, NIHSS, infarct volume, and Fazekas grading (OR = 1.06, 95% CI 1.004–1.11, p = 0.03). Furthermore, the progression group exhibited significantly elevated p-NfH levels in comparison to the stable group. The ROC curve analysis revealed that the ideal cutoff point for p-NfH was determined to be at 166.03 pg/ml. This cutoff point exhibited a sensitivity of 0.774 and a specificity of 0.926 (p < 0.01). Furthermore, the area under the curve was calculated to be 0.881 (95% CI 0.791–0.97, p < 0.01). Serum p-NfH is a potential biomarker for predicting PSCI. Further investigation should explore its potential as an indicator for timely cognitive intervention in stroke patients during follow-up.